Analisis Dampak Sosial Ekonomi Masyarakat Sekitar Pertambangan Batubara Desa Air Putih Kabupaten Bengkulu Utara - Oktaviani, Putri; Bangsu, Tamrin; Afrita, Desy (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Air Putih Village is one of the villages in Marga Sakti Sebelat District, North Bengkulu Regency, where there is a mining area that has been operating since 2014. The existence of mining activities in an area will have various social and economic impacts on the surrounding community. Damage to the natural environment is often the main focus of every mine, however, the socio-economic impact must not be ignored. Therefore, the focus of this research aims to identify the social and economic impacts of the existence of coal mines on the lives of the people of Air Putih Village, Marga Sakti Sebelat District, North Bengkulu Regency. This research is descriptive research with a qualitative approach regarding the impacts felt by residents around the coal mining area. Data was collected through interviews with the community using a random sampling method. People were taken randomly based on the criteria of people living and settling in Air Putih Village. The research results show that the community feels social and economic impacts in the form of funding for the construction of public facilities, assistance with holiday celebration activities in the village, new road access and other material support, and the opening of new job opportunities. This socio-economic impact is felt by the community directly and indirectly, impacting the community around the mine.